The impact of fatigue on performance and biomechanical variables - A narrative review with prospective methodology - Aquino, M.; Petrizzo, J.; Otto, R. M.; Wygand, J. (Biomechanics, 2022)
Landing kinetics and kinematics have historically been correlated with potential injury. A factor that requires more attention associated with its correlation to injury risk includes the impact of physiological fatigue. Fatigue is a multifaceted phenomenon involving central and peripheral factors resulting in a slowing or cessation of motor unit firing and a decrease in maximal force and power. Sports participation rarely results in momentary muscular failure occurring, as many sports consist of intermittent periods of activity that are interspersed with short rest periods that allow for recovery to take place. However, over the course of the competition, fatigue can still accumulate and can result in impaired performance. Current literature on the topic struggles to replicate the peripheral and central metabolic stresses required to induce a state of fatigue that would be equivalent to athletic exposure. Furthermore, the current literature fails to demonstrate consistency regarding the kinetic implications associated with fatigue, which may be secondary to the inconsistencies associated with fatigue protocols utilized. This article focuses on providing an overview of the current literature associated with fatigue`s impact on the kinetics associated with landing from a jump. The article will provide a prospective methodology utilizing repeat bouts of the Wingate Anaerobic Power Test. The proposed protocol may help further our understanding of the relationship between fatigue and lower extremity biomechanics.